Longitudinal and Vertical Variations of Dissolved Labile Phosphoric Monoesters and Diesters in the Subtropical North Pacific - Yamaguchi, Tamaha; Sato, Mitsuhide; Hashihama, Fuminori; Kato, Haruka; Sugiyama, Takanori; Ogawa, Hiroshi; Takahashi, Kazutaka; Furuya, Ken (Frontiers in Microbiology, 2021)
The labile fraction of dissolved organic phosphorus (DOP)—predominantly consisting of phosphoric esters—is an important microbial P source in the subtropical oligotrophic ocean. However, unlike phosphate, knowledge for labile DOP is still limited due to the scarcity of broad and intensive observations. In this study, we examined the concentrations and size-fractionated hydrolysis rates of labile phosphoric monoesters and diesters along a > 10,000 km longitudinal transect in the North Pacific (23° N; upper 200-m layer). Depth-integrated monoesters decreased westward with a maximum difference of fivefold. Vertical profiles of monoesters in the eastern and western basins showed decreasing and increasing trends with depth, respectively. The monoester-depleted shallow layer of the western basin was associated with phosphate depletion and monoesterase activity was predominant in the large size fraction (> 0.8 µm), suggesting that monoesters are significant P sources particularly for large microbes. In contrast, diester concentrations were generally lower than monoester concentrations and showed no obvious horizontal or vertical variation in the study area. Despite the unclear distribution pattern of diesters, diesterase activity in the particulate fraction (> 0.2 µm) increased in the phosphate-depleted shallow layer of the western basin, suggesting that the targeted diesters in the assay were also important microbial P sources. Diesterase activities in the dissolved fraction (< 0.2 µm) were not correlated with ambient phosphate concentrations; however, cell-free diesterase likely played a key role in P cycling, as dissolved diesterase activities were substantially higher than those in the particulate fraction. The horizontal and vertical variability of labile monoesters in the subtropical North Pacific were therefore predominantly regulated by P stress in particularly large microbes, whereas the distributions of labile diesters and diesterase activities were generally independent of microbial P stress, indicating a more complex regulation of diesters to that of monoesters.